2011
DOI: 10.1016/j.jcrs.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Simple technique for sealing clear corneal wound leaks using a dynamic anterior chamber air bubble

Abstract: Wound leak has been demonstrated in 31% of clear corneal incisions (CCIs) at the conclusion of phacoemulsification surgery. 1 We describe a technique for effectively sealing a clear corneal wound with subsequent confirmation of a watertight seal.Clear corneal phacoemulsification is performed under topical anesthesia, and surgical ports are hydrated. If the wound is leaky, an air bubble is injected into the anterior chamber through the side port so the bubble's diameter is one third to one half the corneal diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…If no horizontal shift or tilt is observed, this indicates that the IOL is stable (40). Finally, the injection of an air bubble into the anterior chamber at the end of cataract surgery exhibits no unfavourable effect on the corneal endothelium and as such protects the endothelium (41) to prevent the inflow of ocular surface fluid (42), to protect from leakage of the surgical insicion (43) and to reduce anterior chamber inflammation following surgery (44). The present study revealed that the anterior chamber depth and intraocular pressure were well maintained in the majority of patients.…”
Section: Discussionmentioning
confidence: 58%
“…If no horizontal shift or tilt is observed, this indicates that the IOL is stable (40). Finally, the injection of an air bubble into the anterior chamber at the end of cataract surgery exhibits no unfavourable effect on the corneal endothelium and as such protects the endothelium (41) to prevent the inflow of ocular surface fluid (42), to protect from leakage of the surgical insicion (43) and to reduce anterior chamber inflammation following surgery (44). The present study revealed that the anterior chamber depth and intraocular pressure were well maintained in the majority of patients.…”
Section: Discussionmentioning
confidence: 58%
“…14,15 IABT has also been reported as a special technique to prevent ocular surface uid in ow at the end of sutureless cataract surgery and to prevent postoperative corneal edema. [16][17][18] Moreover, air bubble in AC after cataract surgery can even decrease the rate of DMD when displayed in detail with anterior segment optical coherence tomography. 19 While in experiential animal models, it has the capability to reduce intraocular in ammation, and to prevent endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%